Answer:
C
Step-by-step explanation:
We want the equation of the line that passes through (3, 6) and is perpendicular to:
![3x-4y=-2](https://tex.z-dn.net/?f=3x-4y%3D-2)
First, convert the second equation into slope-intercept form:
![-4y=-3x-2\Rightarrow \displaystyle y=\frac{3}{4}x+\frac{1}{2}](https://tex.z-dn.net/?f=-4y%3D-3x-2%5CRightarrow%20%5Cdisplaystyle%20y%3D%5Cfrac%7B3%7D%7B4%7Dx%2B%5Cfrac%7B1%7D%7B2%7D)
So, we can see that the slope of the line is 3/4.
The slopes of perpendicular lines are negative reciprocals of each other.
Therefore, the slope of the new line is -4/3.
It passes through the point (3, 6).
We can use the point-slope form:
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
Substitute:
![\displaystyle y-(6)=-\frac{4}{3}(x-3)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y-%286%29%3D-%5Cfrac%7B4%7D%7B3%7D%28x-3%29)
Distribute:
![\displaystyle y-6=-\frac{4}{3}x+4](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y-6%3D-%5Cfrac%7B4%7D%7B3%7Dx%2B4)
Therefore:
![\displaystyle y=-\frac{4}{3}x+10](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D-%5Cfrac%7B4%7D%7B3%7Dx%2B10)
The answer is C.